Current Self-Medication Practices and Literacy among People in Yogyakarta Province, Indonesia: A Cross-Sectional Study - Ekasari, Marlita Putri; Kristina, Susi Ari; Yuliani, Rizka Prita (Majalah Farmaseutik, 2024)
In developing countries, self-medication is now becoming a common lifestyle as primary health care. Despite the benefits, the current challenges of inappropriate self-medication practices have potential risks for drug abuse and can lead to drug resistance. Therefore, the aim of this descriptive cross-sectional study was to assess the practice of self-medication related to public knowledge and health literacy in Yogyakarta Province among a sample of 954 respondents who consented to fulfill a validated questionnaire. A convenience sampling approach was applied. Descriptive analysis was performed to describe knowledge and practice of self-medication, and a chi-square test was used for bivariate analysis (p<0.05). The majority of respondents are female (62.58%) with age more than 50 years old (32.91%), and have chronic diseases (38.26%). Moreover, 43.29% of respondents have a low educational background. The results showed predominantly of the respondents had poor knowledge (51.39%) and lack of medicine literacy (53.88%). It seems educational background and chronic medical conditions are associated with the poor practice of self-medication. In conclusion, respondents in Yogyakarta had low knowledge and health literacy level of self-medication and it performs a poor practice. Health education of self-medication should be considered to improve the appropriate practices, especially among individuals with chronic diseases.